Porphyria cutanea tarda and Sjogren's syndrome() - Fang, Su (Sociedade Brasileira de Dermatologia, 2014)
Porphyria cutanea tarda is prevalent in connective tissue disease, common in systemic lupus erythematosus. However, the co-existence of primary sjogren's syndrome and porphyria cutanea tarda is rare and poses diagnostic and therapeutic challenges. We report a case of porphyria cutanea tarda associated with primary sjogren's syndrome.